2023
DOI: 10.3390/molecules28083612
|View full text |Cite
|
Sign up to set email alerts
|

7-Geranyloxycinnamic Acid Isolated from Melicope lunu-ankenda Leaves Perturbs Colon Cancer and Breast Cancer Cell Lines’ Growth via Induction of Apoptotic Pathway

Abstract: Globally, breast cancer is the most prevalent form of cancer in women and there is a need for alternative therapies such as plant-derived compounds with low systemic toxicity and selective toxicity to cancer cells. The aim of this study is to assess the cytotoxicity effects of 7-geranyloxycinnamic acid isolated from leaves of Melicope lunu-ankenda, a traditional medicinal plant, on the human breast cancer cell lines. Dried leaf powder was used for the preparation of different crude extracts using different sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…[39] It was also reported that the compound possessed the ability to induce apoptosis through the accumulation of ROS and activation of caspases in the breast cancer cell lines. [39]…”
Section: Melicope Species and Their Chemical Constituents 21 Melicope...mentioning
confidence: 97%
See 3 more Smart Citations
“…[39] It was also reported that the compound possessed the ability to induce apoptosis through the accumulation of ROS and activation of caspases in the breast cancer cell lines. [39]…”
Section: Melicope Species and Their Chemical Constituents 21 Melicope...mentioning
confidence: 97%
“…In a recent study, 7‐geranyloxycinnamic acid was isolated from the leaves of M. lunu‐ankenda which showed selective cytotoxicity against breast cancer cell lines namely MCF‐7 and MDA‐MB‐231 at IC 50 of 4.936±0.345 and 5.368±0.777 μg/mL respectively [39] . It was also reported that the compound possessed the ability to induce apoptosis through the accumulation of ROS and activation of caspases in the breast cancer cell lines [39] …”
Section: Melicope Species and Their Chemical Constituentsmentioning
confidence: 99%
See 2 more Smart Citations